2021
DOI: 10.1016/j.fertnstert.2021.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Men born small for gestational age or with low birth weight do not improve their rate of reproduction over time: a Swedish population-based study

Abstract: Objective: To investigate whether the reduced reproductive rate among men born small for gestational age (SGA) or with low birth weight (LBW) is present after up to 44 years of follow-up. Design: Population-based register study. Setting: National registers in Sweden. Patient(s): All men born in Sweden between 1973 and 1993 (n ¼ 1,045,167) followed up to 2018. Intervention(s): None. Main Outcome Measure(s): Registered fatherhood, infertility diagnoses, and fertility treatments obtained from registers up to 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…As a result, the ratio of male to female spontaneous abortions exceeds one in clinically recognized (i.e., after about 8 weeks of gestation) pregnancies [ 18 ]. The theory of selection in utero attributes this high ratio to the fact that males small at birth produce fewer offspring than do other males [ 19 ]. This relatively low reproductive fitness presumably arises, at least in part, from the relative frailty of small male infants.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the ratio of male to female spontaneous abortions exceeds one in clinically recognized (i.e., after about 8 weeks of gestation) pregnancies [ 18 ]. The theory of selection in utero attributes this high ratio to the fact that males small at birth produce fewer offspring than do other males [ 19 ]. This relatively low reproductive fitness presumably arises, at least in part, from the relative frailty of small male infants.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades emerging data has shown that in utero conditions might affect offsprings’ reproductive potential. In particular LBW, which is commonly used as a surrogate for impaired fetal growth and development, has been recognized to affect individual long-term somatic health as well as the gonadal and reproductive function [ 19 21 ]. Previous studies have explored the association between LBW and conventional semen parameters, but its impact on SDF and ART outcomes is currently poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether being born with LBW could affect ART outcomes is still unknown. Liffner et al [ 19 ], in their Swedish population-based registry study, analyed data from 21,353 participants attending IVF clinics. They found that men born SGA were more likely to have needed donated spermatozoa to become fathers and were more likely to have used ICSI than men born appropriate for gestational age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations